Equality Before the Law and Distributive Justice in Indonesia’s Private-to-State University Conversion - As Ari AM, Muhammad; Irabiah, Irabiah; Haerani, Yeny; Sari, Patma; Rosnida, Rosnida; Aksan Akbar, Muhamad; Suswanto, Beni (Institut Agama Islam Negeri Kendari, 2026)
Equality before the law is a foundational principle of any state based on law, requiring that all citizens be treated equally without discrimination; in Indonesia it is constitutionally guaranteed by Article 27 paragraph (1) of the 1945 Constitution. Its realisation nevertheless remains contested where policy produces uneven outcomes for parties in comparable positions. This article examines the 2014 policy converting several private universities (PTS) into new state universities (PTN-B), under which the government recruited external candidates for appointment as state civil apparatus (ASN) while long-serving lecturers and education personnel who had built and sustained the converted institutions were excluded from equivalent treatment. Employing a normative legal method that integrates a statute approach, a conceptual approach, and a case approach centred on Universitas Sembilanbelas November Kolaka, the study analyses the relevant constitutional provisions, the State Civil Apparatus Law, employment legislation, and comparative acquired-rights instruments through grammatical, systematic, and teleological interpretation. The analysis finds a significant gap between the normative guarantee of equality and administrative practice. Excluding long-serving personnel from ASN appointment while recruiting external candidates violates both substantive legal equality and distributive justice, because procedural legality does not by itself secure a just distribution of rights and opportunities. Measured against the Rawlsian difference principle, the Aristotelian principle of proportionality, and Stahl’s protective conception of the rechtsstaat, the policy privileges formal certainty over substantive justice. The study recommends reformulating ASN appointment policy and enacting explicit transitional-justice provisions so that institutional transformation upholds rather than erodes equality before the law.